Comparison of the asymmetries in muscle mass, biomechanical property and muscle activation asymmetry of quadriceps femoris between patients with unilateral and bilateral knee osteoarthritis - Chen, Weijian; Li, Congcong; Wang, Yi; Shen, Xingxing; Wu, Zugui; Li, Junyi; Ye, Zixuan; Xiang, Ruian; Xu, Xuemeng (Frontiers in Physiology, 2023)
Background: More and more attention has been paid to the research of muscle mass and muscle quality of quadriceps femoris (QF) in knee osteoarthritis (KOA).This study aimed to explore the asymmetric changes of muscle mass, biomechanical property and muscle activation in the inter-limbs QF of KOA patients, and tried to provide a novel insight for the evaluation, prevention and treatment of KOA.Methods:as shown in follow. Result: Thickness of RF, VI and VL of RSL was lower than those on RML (p < 0.05), and thickness of VM was lower more significant (p < 0.01). Thickness of RF, VI and VL of RSL was also lower than those of RML in BG (p < 0.05), however, there was no significant difference in VM thickness (p>0.05). There were no significant difference in Asymmetry indexes of all measured muscle thickness between the two groups (p>0.05). The Shear modulus of RF, VM, and VL in the RML of UG and BG was higher than those in the RSL (p < 0.05). In sitting and straight leg raising task, the RMS of RF, VM and VL in RML were higher than those in RSL, UG and BG both showed this trend (p < 0.05). About squatting task, in UG, the RMS of the three muscles in RML of patients were also higher than those in the RSL(p < 0.05). However, the difference was not significant in BG(p ＞0.05). In the straight leg raising task, the asymmetry indexes of RMS in RF, VM and VL of both the two groups were positively correlated with VAS scores (p < 0.05).Conclusions: The muscle thickness, shear modulus and muscle activation electromyography of QF in RML were higher than those of RSL in unilateral KOA patients. The VM of RML in bilateral KOA patients may show muscle thickness degeneration earlier, which is closer to the VM of RSL.The shear modulus of RF, VM, and VL were higher on the RML side during the single-leg task, but there may be passive compensation for muscle activation in both lower limbs during the bipedal task.